The Effect Of Student Learning Preparation On The Achievement Of Mathematics Learning In Squadrate And Square Roots Of Round Numbers On High Junior School Students - Sarles Elbinus Barutu (Educare: Journal Educational and Multimedia, 2023)
The problem in this study is how students' learning readiness and how students' mathematics learning achievement, to know the data description of students' readiness in learning mathematics, knowing the description of students' mathematics learning achievement data, knowing whether there is a positive effect of student learning readiness on students' mathematics learning achievement. The population in this study were 139 students of class VII High Junior School. The sample in this study was 29% of the total population, namely 40 people. The samples were taken by a random method. The data collection tools used in this study were a questionnaire totaling 30 items and a test totaling 10 items. Then the data are collected, processed, and analyzed. The results showed that: (1) The average student learning readiness was 79.95 and the standard deviation was 10.536 (2) the students' average mathematics learning achievement was 8.825 and the standard deviation was 1.17 (3) The determination index was 0.92 which means the variable Student learning readiness (Xi) has an effect of 92% on students' mathematics learning achievement (4) There is a positive effect of student learning readiness on mathematics learning achievement of junior high school students